Vaccination against tuberculosis in badgers and cattle: an overview of the challenges, developments and current research priorities in Great Britain. (26th July 2014) - Chambers, M. A.; Carter, S. P.; Wilson, G. J.; Jones, G.; Brown, E.; Hewinson, R. G.; Vordermeier, M.
Abstract : Bovine tuberculosis (TB) is a significant threat to the cattle industry in England and Wales. It is widely acknowledged that a combination of measures targeting both cattle and wildlife will be required to eradicate bovine TB or reduce its prevalence until European official freedom status is achieved. Vaccination of cattle and/or badgers could contribute to bovine TB control in Great Britain, although there are significant gaps in our knowledge regarding the impact that vaccination would actually have on bovine TB incidence. Laboratory studies have demonstrated that vaccination with BCG can reduce the progression and severity of TB in both badgers and cattle. This is encouraging in terms of the prospect of a sustained vaccination programme achieving reductions in disease prevalence; however, developing vaccines for tackling the problem of bovine TB is challenging, time‐consuming and resource‐intensive, as this review article sets out to explain.